Essays in the economic of socialism and capitalism : selected papers read to Section F of the British Association for the Advancement of science, 1886-1932 - Smyth, R. L. (ed.) (London, 1964)
The contents of this volume have been assembled by selecting papers which, because of their quality and the reputation of their authors, simply could not be excluded: Jevons on Sunspots, Marshall on Competition, a hitherto unpublished paper by Sidney Webb, George Bernard Shaw on Socialism, Sir Robert Giffen on Economic Progress, Beveridge on Unemployment and Schumpeter on Capitalism. As can be seen from the Bibliographies of Section F papers (1860-1913 included in volume I and 1919-39 in this volume), the decision to restrict papers to four topics did not unduly restrict the choice of "supporting " papers. In his Introduction Professor Wilson considers the connections between the papers and their authors which ensure that this is a reasonably coherent collection of essays.
Keywords: Socialism